Upstream Security: 2020 Global Automotive Cyber security Report. Issue 1 (January 2020) - Unknown
Abstract : Not very long ago, the concept of having to perform software updates for your car would have seemed bizarre. Today's vehicles, however, are just more nodes on the network. From streaming music, providing traffic data and keyless operation through to battery management and telematics, cars now bristle with computers and communications capabilities.